On the automorphism group of certain simple C^*-algebras - Mygind, Jesper (MATHEMATICA SCANDINAVICA, 2004)
We show that the information contained in KL(A,B) is determined by other invariants when A and B are certain simple unital projectionless C^*-algebras. This allows us to compute the group of automorphisms modulo the group of approximately inner automorphisms in terms of the Elliott invariant.